2018
DOI: 10.1002/pon.4732
|View full text |Cite
|
Sign up to set email alerts
|

Exploring cancer survivors' views of health behaviour change: “Where do you start, where do you stop with everything?

Abstract: For many participants in this study, the period that follows treatment for cancer did not represent a "teachable moment." A variety of complex and heterogeneous factors appeared to impact motivation and may limit cancer survivors from engaging with diet and PA changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(60 citation statements)
references
References 30 publications
8
51
0
1
Order By: Relevance
“…Weaver et al [33], found that just one in three cancer survivors reported having had a health promotion discussion with their health care provider. It has also been found that some survivors are unsure about how to make changes and perceive a lack of support from their health care team [35]. Lifestyle interventions are known to bring about positive lifestyle changes that result in improved health and functioning [36], and these changes should be a primary goal for cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Weaver et al [33], found that just one in three cancer survivors reported having had a health promotion discussion with their health care provider. It has also been found that some survivors are unsure about how to make changes and perceive a lack of support from their health care team [35]. Lifestyle interventions are known to bring about positive lifestyle changes that result in improved health and functioning [36], and these changes should be a primary goal for cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to our finding that support from health professionals was associated with adoption of a healthy diet, we also found that lack of knowledge made it less likely to make dietary changes. After completion of treatment, cancer survivors may report feeling abandoned and express uncertainty about how to implement adaptive changes (Corbett et al, 2018). The reason for this uncertainty is that the patient often has limited knowledge of beneficial healthy behaviors, and lacks support in identification of evidence-based information on how to implement adaptive changes (Henry et al, 2016;James-Martin et al, 2014;Koutoukidis et al, 2017).…”
Section: Tablementioning
confidence: 99%
“…Many cancer patients are motivated to adopt healthy diets following completion of treatment, but these barriers could counteract these motivations. Recent qualitative studies of overall cancer survivors (Corbett et al, 2018), prostate cancer patients (Er et al, 2017), breast cancer patients (Terranova et al, 2017), and adolescent and young-adult cancer patients (Wu et al, 2015) identified barriers and facilitators to adoption of healthy eating. However, no study has yet identified factors that function as barriers and motivators for adopting a high-quality diet in survivors of stomach cancer.…”
Section: Introductionmentioning
confidence: 99%
“…at a time when individuals may be particularly receptive to advice and motivated to make changes). However, an English study has highlighted that a cancer diagnosis may not necessarily represent a ‘teachable moment’ for everyone (Corbett et al ). Although some individuals make positive lifestyle changes following treatment, others may not engage with diet and physical activity recommendations.…”
Section: Nutrition and Physical Activity In Cancer Survivors In Scotlandmentioning
confidence: 99%
“…Although some individuals make positive lifestyle changes following treatment, others may not engage with diet and physical activity recommendations. Reasons for a lack of engagement vary, including a belief that behaviour change is unnecessary or undesirable, uncertainty about how to implement recommendations for improvement, or a perceived lack of support from healthcare providers (Corbett et al ). Therefore, in addition to providing information on recommendations, interventions to improve diet and physical activity in cancer survivors must address barriers to implementing recommendations.…”
Section: Nutrition and Physical Activity In Cancer Survivors In Scotlandmentioning
confidence: 99%